Assessment of mechanical properties of Silicon Carbide and Graphene reinforced aluminium composite. (2020) - Saravanan, C.; Dinesh, S.; Sakthivel, P.; Vijayan, V.; Kumar, B.Suresh
Abstract: Metal Matrix Composite is widely replacing the older materials in the area of aerospace applications. The evolving requirement of superior properties and increased lifetime expectancy has led to formation of newer composite materials. An attempt has been made to formulate and evaluation of the fundamental properties of the developed composite. AA 7075 aluminium material is reinforced with fixed percentage of Silicon Carbide and Graphene in different proportions. Three samples were made and mechanical properties and Microstructural properties were studied. The graphene was increased by order of 3% of net weight of composite varying from 0% to 6%.